An Information Mediator Network for Tasks in Dynamic Environments - Patil, R.; Zhang, W.; Shen, W. (Yearbook of Medical Informatics, 1996)
Coordination of activities among information workers and services, tracking and managing activities, and intelligent distribution of information are essential to the efficient operation of any large enterprise. This is particularly important in the healthcare domain, where many different organizations must cooperate to provide patient care reliably in a dynamically changing environment. In this review paper we present a distributed system that supports cooperative problem solving, activity management, and intelligent delivery of information in dynamic and unreliable environments. The system consists of a network of task/context managers (TCMs). Each TCM manages a group of related agents. It maintains up-to-date information on availability, operational status, and activities of participating agents, and it acts as a mediator between service requesters and service providers. In addition, the TCM acts as a representative for its agents with other TCMs, allowing different groups of agents to collaborate with one another. This paper describes the system architecture, its implementation and capabilities including matchmaking, plan monitoring, and failure recovery. Our system has been used in prehospital emergency patient information management applications.
Keywords: Distributed Agents; Medical Workstation; Software Engineering.